Vertical Electrical Sounding Exploration of Groundwater in Kertajati, Majalengka, West Java, Indonesia - Nugraha, Gumilar Utamas; CSSSA, Boy Yoseph; Nur, Andi Agus; Pranantya, Pulung Arya; Handayani, Lina; Lubis, Rachmat Fajar; Bakti, Hendra (Geological Agency, 2021)
Continuously increasing population and progressive infrastructural development in the region of Kertajati International Airport, Indonesia, emphasize the need to develop a sustainable water supply network. Airport facilities require sufficient water resources, which can be obtained from surface water and groundwater. Groundwater exploration can provide necessary information for assessing water resources. The purpose of this study is to analyze the configuration of aquifers in the studied area. A Schlumberger array was used to carry out twelve vertical electrical soundings (VES) with AB/2 electrode spacing ranging from 1.5 m to 150 m. IPI2win software was used to qualitatively interpret the VES results and it suggested the presence of three distinct lithological units interpreted as clay, alluvial sand, and a Lower Quaternary formation. In general, resistivity values in the studied area can be divided into five resistivity categories: very low resistivity with values ranging from 1 Ωm to 10 Ωm, low resistivity with values ranging from 10 Ωm to 50 Ωm, medium resistivity with values ranging from 50 Ωm to 100 Ωm, high resistivity with values ranging from 100 Ωm to 200 Ωm, and very high resistivity with values > 200 Ωm. The geo-electric interpretation revealed three geo-electric layers: topsoil (1 - 144 Ω m), sand (1 - 298 Ω m), and clay (1 - 82 Ω m). Aquifers in the studied area are lithologically composed of sand. Clay is the dominant lithology in the studied area, so the presence of aquifers in this area is very limited, and thus the supply of groundwater is also limited. The exploitation of groundwater must be limited and controlled to maintain the sustainability of groundwater in the studied area.